MEMAKNAI PERANG BARATAYUDHA DALAM PERSPEKTIF KITAB KELUARAN (EXODUS) - Wiwid Widyaswoko (Sekolah Tinggi Theologia Abdiel, 2018)
This article discusses and compares between the story of the war of Baratayudha and that of the Exodus in the Old Testament. The writer tries to give meaning about the war of Baratayudha from the perspective of the theology of the war from the Exodus. In the Exodus, God have always defended the oppressed people when war happened. God was with the oppressed people and He gave freedom to them. In the war, God did not only have aim to show His power but to destroy the evil.